2021
DOI: 10.1002/ece3.8384
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator individual‐based networks reveal the specialized plant–pollinator mutualism in two biodiverse communities

Abstract: The interactions between plants and their pollinators are considered to be one of the fundamental drivers of angiosperm diversity (Stebbins, 1970). The specialization of the pollination system is important for a successful pollination, since a high level of specialization would assure conspecific pollen transfers within plant species and a high energy intake rate of pollinators (Johnson & Steiner, 2000). Local populations of entomophilous plant species would benefit from specializing foraging bouts of pollinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…For example, we found that the flowers of D. sophia and Angelica nitida could attract more than ten pollinator species. Additionally, our results showed that the main pollinator species were flies, bees, and butterflies (Figure 2), which are generalized pollinators that can visit many flowering plants in alpine grasslands (Wang et al, 2021). Therefore, we could not determine any changes in pollinator diversity and abundance due to P and N addition (Burkle and Irwin, 2009;Villa-Galaviz et al, 2021).…”
Section: Weak Effects Of Structural Changes In Flowering Plants On Po...mentioning
confidence: 84%
See 2 more Smart Citations
“…For example, we found that the flowers of D. sophia and Angelica nitida could attract more than ten pollinator species. Additionally, our results showed that the main pollinator species were flies, bees, and butterflies (Figure 2), which are generalized pollinators that can visit many flowering plants in alpine grasslands (Wang et al, 2021). Therefore, we could not determine any changes in pollinator diversity and abundance due to P and N addition (Burkle and Irwin, 2009;Villa-Galaviz et al, 2021).…”
Section: Weak Effects Of Structural Changes In Flowering Plants On Po...mentioning
confidence: 84%
“… Burkle and Irwin (2009) also found that N addition did not affect the richness of pollinator communities. A possible explanation might be that most of the remaining flowering plant species, such as Asteraceae, Ranunculaceae, and Rosaceae, had an open morphology with radially symmetrical flowers in the nutrient-addition plots ( Figure 2 and Supplementary Table 1 ), which could attract many generalized pollinator species to visit these flowering plants ( Duan et al, 2007 ; Zhang et al, 2015 ; Wang et al, 2021 ). For example, we found that the flowers of D. sophia and Angelica nitida could attract more than ten pollinator species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This form of network representation shows levels of generalism or specialism for each species but effectively assumes similar interaction preferences per individual within a given species. However, individuals within species can vary in their dietary breadth (Tur et al, 2014;Wang et al, 2021), level of 'generalism' (Arroyo-Correa et al, 2023) and interaction plasticity (Araújo et al, 2008 andTinker et al, 2012 for food web examples). As a result, in individual-level networks, individuals within the same module may not necessarily be of the same species (in Tur et al, 2015, this is due to phenology).…”
Section: Box 2 Moving From Species-to Individual-level Networkmentioning
confidence: 99%
“…Network structure may not be consistent across hierarchical scales of organization (Tur et al 2014, Wang et al 2021). To begin with, the similarity in the set of partners available to individuals of the same species will be higher than that to different species.…”
Section: Introductionmentioning
confidence: 99%